Ultrafast quasiparticle dynamics in Tl2Ba2CuO6+delta - Smith, D; Gay, P; Wang, D; Wang, J; Ren, Z; Ryan, J (2000)
We present measurements of the ultrafast time-resolved reflectance of optimally doped Tl2Ba2CuO6+delta. The superconducting state response is interpreted in terms of pair formation from non-equilibrium quasiparticles in the nodes of a d-wave superconducting gap. For T greater than or similar to T-c the response shows evidence for dynamic superconducting fluctuations.